A Dynamic Bayesian Network Based Merge Mechanism for Autonomous Vehicles - Zine el Abidine, Kherroubi; Samir, Aknine; Rebiha, Bacha (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
This work explores the design of a central collaborative driving strategy between connected cars with the objective of improving road safety in case of highway on-ramp merging scenario. Based on a suitable method for predicting vehicle motion and behavior for a central collaborative strategy, a dynamic Bayesian network method that predicts the intention of drivers in highway on-ramp is proposed. The method was validated using real data of detailed vehicle trajectories on a segment of interstate 80 in Emeryville, California.